Effect of Citric Acid, Aluminum and It’s Interaction in The Seedling Growth of Soybean (Glycine max L.) Varietas Anjasmoro - Radella Hervidea; Zulkifli Zulkifli; Martha Lulus Lande (Politeknik Negeri Lampung., 2016)
The objective of this research was to know whether citric acid was able to decrease effect of aluminum on the seedling growth of soybean (Glycine max L.) varietas anjasmoro. The experiment was conducted in Plant Physiology Laboratory, Department of Biology, Faculty of Mathematic and Natural Science, Lampung University on January 2016 in 2x3 factorial designs. Factor A was aluminum with 2 levels : 0 mM and 5 mM. Factor B was citric acid with 3 levels : 0 mM, 5 mM and 10 mM. Variables in this research were fress weight, dry weight, relative water content and total chlorophyll content. Analysis of variance was conducted at 5% significant level. If interaction was not significant, main effect was determined with lsd test at 5% significant level. If interaction was significant simple effect was determined with F test at 5% significant level. The result showed that the citric acid decreased fress weight, dry weight, relative water content and no effect on total chlorophyll content while aluminum did not affect all variables and no interaction between citric acid and aluminum on all variables. It is concluded that citric acid was not able to inprove seedling growth of soybean varietas anjasmoro with aluminum or no aluminum. Keyword : Citric acid, Aluminum, Soybean, Frees weight , dry weight